Efisiensi Ekonomi dan Kelayakan Bisnis pada Sistem Budidaya di Pesisir Kabupaten Sidoarjo, Jawa Timur - Hukom, Venticia; Kusumastanto, Tridoyo; Djokosetyanto, D. (Jurnal Aplikasi Manajemen, 2013)
Producing shrimps within ecological carrying capacity and economic feasibility seems to be the goal needed to be achieved in order to bring back Sidoarjo to be one of the biggest districts exporting shrimps. Decision makers, i.e. policy makers and farmers are challenged with the responsibility of planning and conducting aquaculture development in a sustainable way whereby social, ecological and economic goals are simultaneously satisfied. Cobb-Douglas Production Function is one of the methods used to know which input highly affects the shrimp production, continued by Investment Analysis i.e. Discounted Criteria methods that include NPV, Net B/C and IRR to see which system is feasible. As for ecological sustainability, this research uses water quality data translated into Pollution Index as an indicator. And from survey that has been done in Sidoarjo district from May 2013 to October 2013, using Pollution Index analysis show that ponds in Sidoarjo are moderately polluted, the next analysis using regression for Cobb-Douglas Production Function stated that in traditional system production factors that statistically significant arepond area, harvest and pond preparation labour, dissolved oxygen and ammonia. In traditional plus system, pond area, fertilizer, saponin and ammonia seems to be statistically significant. The best shrimp cultivation system would be Traditional Plus Polyculture between shrimp and milkfish that has NPV IDR 6.036.817.617, Net B/C 2,91 and IRR 51% compared to other systems such as Traditional Monoculture, Traditional Plus Monoculture and Traditional Polyculture.